Precocious puberty: a question to be answered. Issue 2 (June 2016) - Mostafa, Taymour
Abstract : Precocious puberty (PP) is allied with accelerated growth, advanced bone age, development of secondary sex characteristics, and early closure of epiphysis. This article aimed to review PP in both sexes. A search for a review of published articles was carried out using PubMed, medical subject heading databases, and Scopus engine. Keywords used to accomplish these concerned associations were puberty, PP, adolescence, adrenarche, menarche, pubarche, and thelarche. Etiologically, PP is divided into gonadotropin-releasing hormone (GnRH)-dependent and GnRH-independent causes. GnRH-dependent PP [central precocious puberty (CPP)] is based on hypothalamic–pituitary–gonadal axis activation associated with progressive pubertal development, accelerated growth rate, and advanced skeletal age. CPP is one of the common forms of PP resembling the normal route of puberty at an age less than 8 and 9 years for girls and boys, respectively. Peripheral precocious puberty is related to sex steroid exposure independent of hypothalamic–pituitary–gonadal axis activation. Therapy is indicated in children with CPP with accelerated bone age, height progress, or psychosocial stress to halt puberty succession to a socially satisfactory age, allowing the child to achieve optimal height potential. GnRH analog is the treatment of preference, with best height result if initiated before 6 years of age.